Consumo de frutas frescas no município de Alto do Rodrigues - RN - Rocha, Alessandra Silva da (Universidade Federal Rural do Semi-Árido, 2019)
The quality of the product is directly linked to its consumption, representing today in Brazil, great generator of employment and income. The objective of this study was to evaluate the frequency of fresh fruit consumption and the perception of consumers regarding the quality aspects of fresh fruit in the municipality of Alto do Rodrigues in the state of Rio Grande do Norte. In the process verifying the possible interrelations with the age group, sex, educational level and income, with application of questionnaires with consumers of fruit in the markets and free fair of the city. The variables presented were: price; appearance, taste and aroma; packing; regularity of supply (ease of finding the product); lifespan; absence of agrochemical residues; nutritional value; functional value; others. The statistical procedure adopted was the presentation of the results in a descriptive way. All respondents stated that they consume at least one kind of fruit, with daily and weekly consumption. Among the most cited types of fruit were banana, apple, orange, papaya and watermelon. Most of the interviewees affirm that the taste and aroma, appearance and price are the main aspects for the consumption or not of the fruit.
Monografia
Keywords: Perfil de Consumidor; Qualidade de frutas frescas; Pós-colheita; Profile Consumer; Fruit quality; Post-harvest; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA